The Polish Banking System In A Historical Approach: From Systemic Transformation To The European Union (Economic and Political Thought, 2021)
The orientation towards economic development, as well as the social determination to join the European Union (EU), were among the main motives behind the reforms of Polish public institutions and changes to neoliberal economic policy. Thus, the main goal of this article is to conduct an in-depth analysis of the above-mentioned transformations that took place in Poland after 1989, focusing on the institutional adjustments introduced in the banking sector. Applying the institutional approach, the considerations arebased on the main stages of its formation and development (including the legislative milestones), as well as its adaptation to future membership in the EU. At the same time, in order to provide the reader with a more comprehensive perspective of the Polish case, the time frame of the deliberations is being extended to the period corresponding to the recent Great Recession, comprised of the economic and financial crisis (2008) and the debt crisis (2010), as well as completed with final thoughts about the possible influence of the pandemic by COVID-19.
Keywords: Poland, banking sector, systemic transformation, institutional changes, Great Recession, COVID-19